Ursolic acid drug-drug nanocrystals ameliorate cholestatic liver injury via inhibiting oxidative stress and regulating bile acid metabolism - Hu, Manhang; Hua, Xiaolu; Xiong, Wei; Zheng, Enhui; Yang, Xingyue; Lu, Yu; He, Bing; Zhong, Xiaolin; Jiang, Zongzhe; Zhang, Qingbi; Liu, Yan (Frontiers in Pharmacology, 2025)
IntroductionCholestatic liver injury (CLI) is a liver dysfunction closely associated with oxidative stress and bile acid (BA) metabolic disorders, but effective therapies are lacking.The use of ursolic acid (UA) and α-Tocopherol succinate (VES) together for treating CLI is promising due to their respective effects on regulating bile acid metabolism and providing antioxidant activity.MethodsIn this study, we synthesized drug-drug nanocrystals (UA-NSps) composed of UA and VES to treat CLI and evaluated their synergistic therapeutic effects by regulating bile acid metabolism and inhibiting oxidative stress in ANIT-induced CLI mice.Results and discussionOur investigation demonstrated that UA-NSps exhibited high drug-loading capacity, spherical morphology, and improved dissolution and oral bioavailability. In the ANIT model, UA-NSps effectively restored liver function, as evidenced by histopathological and biochemical improvements. Mechanistically, UA-NSps enhanced Nrf2 nuclear translocation, upregulated Nrf2 and HO-1, reduced pro-inflammatory cytokines, and ameliorated mitochondrial damage. Moreover, UA-NSps alleviated the bile acid metabolism disorders by upregulating the transcriptional activity of UGT2B1, BSEP, and MRP2, as well as the protein expression of nuclear receptors and metabolic enzymes PXR,CYP3A4, and UGT1A1. Our study presents a novel drug-drug nanocrystal strategy that enhances the therapeutic efficacy against CLI by inhibiting oxidative stress and regulating bile acid metabolism.